Product Innovation and Consumer Preference for Feminine Hygiene Products: A Moderated Model with Product Deprivation - Gautam, Prakash Kumar; Khadka, Srijana (Management Dynamics, 2022)
The study aimed to analyze the impact of product innovation on consumer preferences for feminine hygiene products. The study also investigated the mediated and moderated influence of deprivation on the adoption of the product. Following the analytical research design and deductive approach, the study has been conducted by adopting a multistage sampling method among the females dwelling in Kathmandu, economically active in different sectors, and with active menstrual cycles. The structured questionnaire prepared by adapting validated variables was used to collect the data from 385 respondents working in 50 organizations. Descriptive and inferential analysis was done using Process Macro for mediation and moderation effects using Hayes (2017) models. The study concludes that product innovation significantly impacts consumer preference, with a positive interactive moderation effect of deprivation with product innovation for consumer preference in feminine hygiene product adoption.